Ten questions concerning the use of drones in urban environments. (January 2020) - Watkins, S; Burry, J; Mohamed, A; Marino, M; Prudden, S; Fisher, A; Kloet, N; Jakobi, T; Clothier, R
Abstract: The backdrop to the rapidly expanding use of drones is described, including development of drone technology, followed by an overview of current civilian use, focusing on use in and around the urban environment. The inhibitors to further use are considered including technological and societal aspects. The operation and control issues are reviewed including autonomous or semi-autonomous operation. Issues of lack of regulation, safety, lack of endurance/payload, noise, inability to fly well in adverse weather are considered. Research into how these issues may be overcome is discussed and comparisons are drawn with how equivalent-sized natural flyers (bird and larger flying insects) cope within the urban environment are made. The paper concludes with an overview of possible and planned use in the urban environment. Highlights: Drones are considered by some as "the most disruptive technology in human history". The opportunities afforded by drones are reviewed. Challenges, including risk, noise and human perception are considered. Limitations of their current technology, such as short endurance and inability to fly under a range of adverse weather conditions, are evaluated. Methods of overcoming limitations are outlined, including incorporating drone-friendly design into new high-rise urban environments.